Development of a Practical E-Module for POE-Based Used Cooking Oil Management in West Sumbawa Regency - Seprianingsih, Dewi; Saputra, Rizka Doni Agung (Postgraduate, University of Mataram, 2023)
The research objectives were to determine: 1) the process of developing POE-based E-module practicum management of used cooking oil in West Sumbawa Regency; 2) expert validation test results (construct/design and content/material) E-module practicum management of used cooking oil based on POE in West Sumbawa Regency by the validator; 3) the results of the E-module readability test for the management of POE-based used cooking oil practicum by students. The development of the POE-Based E-Module Practicum Management of Cooking Oil refers to the 4D learning development model. This research only reached stage 3 D (Develop), namely the development stage with detailed activities in the form of expert validation (construct/design and content/material) by the validator and the E readability test of the POE-based waste cooking oil management practicum module. The instruments to be used in this research are: Construct validation sheet and contents of the practicum E-module and the readability test sheet of the practicum E-module. Based on the results of research that has been carried out, the results of validation I from validator I were obtained with a value of 88%. Meanwhile, the results of validation I from validator II were 89.2% with very valid criteria